It’s not so bad: Director bankruptcy experience and corporate risk-taking - Gopalan, Radhakrishnan; Gormley, Todd A.; Kalda, Ankit (Journal of Financial Economics, 2021)
We show that firms take more (but not necessarily excessive) risks when one of their directors experiences a corporate bankruptcy at another firm where they concurrently serve as a director. This increase in risk-taking is concentrated among firms where the director experiences a shorter, less-costly bankruptcy and where the affected director likely exerts greater influence and serves in an advisory role. The findings show that individual directors, not just CEOs, can influence a wide range of corporate outcomes. The findings also suggest that individuals actively learn from their experiences and that directors tend to lower their estimate of distress costs after participating in a bankruptcy firsthand.